Relationship Between White Matter Integrity and Plasma Leptin Levels in Drug-Naïve and Medicated Patients With Major Depressive Disorder - Amer, Abdulrahman A. A.; Zhu, Yue; Wei, Shengnan; Zhang, Ran; Wang, Yang; Duan, Jia; Jiang, Xiaowei; Tang, Yanqing; Wang, Fei (Frontiers in Neuroscience, 2019)
Many previous studies have noticed obvious alterations in different white matter tracts among patients with major depressive disorder (MDD). Growing evidence also strongly suggest a role of leptin in the pathogenesis of major depressive disorder (MDD), but with conflicting results of leptin levels. However, no previous studies have examined the relationship between leptin and white matter integrity of patients with MDD. Therefore, we aimed in this study to investigate the relationship between white matter alterations and plasma leptin levels in both drug-naïve and medicated MDD patients. We measured plasma leptin levels and white matter integrity using diffusion tensor imaging (DTI) and voxel-based analysis (VBA) in 140 participants (40 drug-naïve MDD patients; 40 medicated MDD patients; 60 healthy controls) aged between 18 and 49 years old. A significant reduced fractional anisotropy (FA) value in the dorsomedial thalamus was found for both drug-naïve and medicated MDD patients compared to the healthy non-depressed participants (p < 0.01, corrected). In addition, leptin levels were significantly higher in the drug-naïve MDD patients and were negatively correlated with the detected white matter alteration. Our results suggest that the elevated plasma leptin levels in the drug-naïve MDD group might be associated with the changes of the white matter integrity in the dorsomedial thalamus region.